Tourists’ Preferences for Preservation of World Heritage Site Stadthuys, Malacca - MAHIRAH, Kamaludin; NAZATUL, Faizah Haron; MOHD, Azrin Shah Razali (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020DO - 10.14505//jemt.v11.2(42).06, 2020)
Preservation of historical buildings and sites is vital to uphold and conserve a nation’s history and heritage. The importance of preservation works on historical buildings and sites in Malaysia towards its tourism industry can be considered as vague, hence the benefit and values of preservation work is still ambiguous. This study estimates willingness to pay (WTP) of domestic tourists for the preservation of UNESCO World Heritage Site (WHS) Stadthuys, Malacca, Malaysia. This study applied Contingent Valuation Method (CVM) through questionnaires which have been distributed to 100 domestic tourists. The results of the CVM were one of the appropriate techniques to estimate the economic value of the cultural and historical preservation works. On average, respondents were willing to pay approximately RM 8.82 for the preservation of the Stadthuys, in which this value was higher than the current fee, RM5. It demonstrated that visitors were willing to contribute in any preservation efforts of the site and the allocation of money can be used as maintenance cost of the heritage. Public involvement in tourism services demonstrates positive influences on protection of cultural heritage and development of local communities too. The originality of this paper is presented how the field of economic valuation denotes to calculate value for sustainable tourism in world heritage sites.